Pendampingan Pemanfaatan Majalah Dinding Kelas untuk Minat Baca Siswa Kelas 4 di SDK Bejo - Meka, Marsianus; Ngura, Elisabeth Tantiana; Lende, Rosalia (Civiliza Publishing, 2025)
This study aims to explore the use of classroom wall magazines as a medium to enhance reading interest among 4th-grade students at SDK Bejo. Classroom wall magazines are a communication tool that can be used to deliver information, educate, and spark students' interest in various topics, including literacy. This research adopts a qualitative approach with observation and interviews conducted with teachers and students in the 4th grade at SDK Bejo. The results of the study show that the use of classroom wall magazines, which feature engaging stories, educational information, and creative visuals, successfully captured students' attention, leading to an increase in their reading interest. Students exhibited high enthusiasm in reading the articles displayed on the wall magazine, and many of them began discussing the topics presented. In addition, teachers also integrated the wall magazine into their teaching activities, supporting the enhancement of students' literacy skills. Therefore, classroom wall magazines have proven to be an effective means of increasing students' reading interest while enriching their learning experience at school.